High normal blood pressure and left ventricular structural and functional disorders in young adults - E. K. Shavarova; I. A. Khomova; Zh. D. Kobalava; E. I. Kirpichnikova; N. E. Ezhova; E. I. Bazdyreva (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the association of a high normal blood pressure (BP) with the risk of early hypertension-mediated organ damage (HMOD) in young adults.Material and methods. Medical screening of population aged 18-45 years (n=987) revealed that in 173 persons, office BP corresponded to a high normal level or hypertension (HTN). Echocardiography (GE Healthcare Vivid 9, using EchoPAC Software) was performed when HTN was confirmed by office BP measurement and/or according to 24-hour ambulatory BP monitoring (ABPM) (n=127). In addition, creatinine and albumin-to-creatinine ratio in spot urine were measured.Results. The median age was 23 [21; 25] years. The median systolic (SBP) and diastolic BP (DBP) was 129 [121; 137] and 75±12 mm Hg, respectively. The detection rate of LV geometry abnormalities was 3,3 times higher in the high normal BP group [95% CI, 1,06-6,28, p=0,02], and 10,7 times higher in the HTN group [95% CI, 2,32-16,49, p=0,04] compared with the optimal+normal BP group. In a multivariate analysis, the independence of associations with the LV mass index (LVMI) was confirmed only for the mean nighttime DBP, left atrial volume index, and the ratio of LV peak early diastolic velocity to the average septal and lateral peak early diastolic mitral annular velocity.Conclusion. In young people, the prevalance of HMOD is comparable in the groups with high normal BP and HTN, while significant differences were found between the group with optimal+normal BP levels and patients with HTN and high normal BP. An independent association of elevated LVMI with mean nighttime DBP was found.